IMPLEMENTASI PROGRAM BEASISWA BIDIKMISI BHAKTI NEGERI UNIVERSITAS RIAU - Lestari, Muharani; Kadarisman, Yoskar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This researc was conducted ar Universitas Riau. The purpose of this research was to determine the implementation of the bidikmisi bhakti negeri scholarship program seen from behavior of studentd in utilizing the scholarship provided, as measured by students’ knowledge, attitudes, and actions. In this study the authors used a descriptive quantitative method and the analysis technique used was the frequency distribution teble and cross tabulation analysis in this study the sampling technique used was total sampling / cencus and the total sample are 90 students. Data collection technique using the questionnaire method. The result showed that the behavior students in using scholarship provided were categorized as moderate behavior (70.0%). Students' knowledge of the targets, objectives, and functions of the bidikmisi bhakti negeri scholarship are categorized as knowing (87.8%). The attitude of students in using funds for academic needs is classified as Poor (70.0%). The attitude of students in using scholarship funds for non-academic needs is well categorized (65.6%). Student actions in improving academic quality are categorized as moderate (64.4%). Thus the implementation of the scholarship provided, the implementation of the program has not fully gone well, because there are still some students in utilizing scholarship is not in line with what is expected by the government.Keywords: Implementation, Bidikmisi Bhakti Negeri Scholarship